A new Brazilian species of Stenochironomus Kieffer mining decayed leaves in bromeliads (Diptera: Chironomidae) - de Pinho, Luiz Carlos; Mendes, Humberto Fonseca; Marcondes, Carlos Brisola (Zootaxa, 2005)
All life stages of Stenochironomus atlanticus Pinho & Mendes sp. n. are described and figured. The larva mines decaying leaves held in the water of several bromeliad species (Canistrum lindenii (Regel) Mez, Neoregelia laevis (Mez) L.B. Smith, Nidularium innocentii Lemaire, Vriesea philippocoburgii Wawra, and Vriesea vagans (L.B. Smith) L.B. Smith.) in the Atlantic Rain Forest in southern Brazil [Desterro Environmental Conservation Unit (Unidade de Conservação Ambiental Desterro – UCAD), Santa Catarina Island]. Stenochironomus atlanticus is the only species in the genus found in the phytotelmata habitat, and it apparently is restricted to this environment.